Activation of the sol–gel process by visible light-emitting diodes (LEDs) for the synthesis of inorganic films. (29th May 2015) - Shi, Suqing; Allonas, Xavier; Croutxé-Barghorn, Céline; Chemtob, Abraham
Abstract : Photosensitized acid generation opens the possibility of using a visible LED light source for inorganic photo sol–gel process. It also provides a simple approach for sustainable synthesis of inorganic or hybrid materials under solar irradiance. Abstract : Photoinduced sol–gel polymerization is an efficient one-step and solvent-free process to synthesize inorganic or hybrid films. Highly condensed films are achieved using photoacid generators (PAGs) producing in situ Brönsted superacids without thermal densification. However, most commercial PAGs exhibit short light absorption below 300 nm and display limited overlapping with the emission spectra of conventional UV sources, or with the newly emerging visible LED light sources. Therefore, the development of PAGs with extended absorption in UVA ( λ > 380 nm) is of paramount importance. In this study, a simple one-step visible LED induced sol–gel process of poly(dimethoxysiloxane) (PDMOS) was conducted by virtue of different photosensitized acid generating systems. The sol–gel process was followed using real-time Fourier transform infrared (RT-FTIR) spectroscopy. The hydrolysis rate and condensation of the siloxane network were directly correlated with the concentration of the photogenerated acid. Different types of photosensitizers, onium cations and counter anions were investigated. Isopropylthioxanthone combined with iodonium salts bearing high charge delocalized anions led to the fastest and more efficient release of protonic acid, yielding tack-free and condensed transparent silica films.